Supporting English Language Development of English Language Learners in Virtual Kindergarten: A Parents' Perspective - Sara Shahbazi; Geri Salinitri (Flexible Learning Association of New Zealand, 2023)
The researchers of this case study explored English language learner (ELL) parents' experience as they supported their children's English language development in an online (virtual) kindergarten programme. One-on-one semi-structured interviews were used to collect data. Then the researchers used thematic analysis to describe the participants' lived experience with the phenomenon. Findings indicated that online learning increased the emotional stressors for parents of ELL children, and altered the communication between parents and teachers. Meanwhile, the use of breakout rooms reinforced the children's language development, and translation services supported parents. Based on the findings, the researchers recommend that schools and boards provide the parents and families of multilingual learners with ongoing workshops to give them the tools and confidence to continue supporting their children in person and online. They also recommend a greater investment in translation services.